2023
DOI: 10.3390/jcdd10090357
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Heart Regeneration: Searching for the Key to Heal the Heart—Part II: Molecular Mechanisms of Cardiac Regeneration

Juan Manuel Castillo-Casas,
Sheila Caño-Carrillo,
Cristina Sánchez-Fernández
et al.

Abstract: Cardiovascular diseases are the leading cause of death worldwide, among which ischemic heart disease is the most representative. Myocardial infarction results from occlusion of a coronary artery, which leads to an insufficient blood supply to the myocardium. As it is well known, the massive loss of cardiomyocytes cannot be solved due the limited regenerative ability of the adult mammalian hearts. In contrast, some lower vertebrate species can regenerate the heart after an injury; their study has disclosed some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 271 publications
(399 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the present study demonstrated that ACP5 promotes the proliferation, migration, and phenotypic transformation of CFs. Although studies have shown differences in ACP5 protein levels in CFs, other cells and effectors, such as extracellular vesicles (Morelli et al 2019 ) and non-coding RNAs (Castillo-Casas et al 2023 ; Jankauskas et al 2023 ), cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present study demonstrated that ACP5 promotes the proliferation, migration, and phenotypic transformation of CFs. Although studies have shown differences in ACP5 protein levels in CFs, other cells and effectors, such as extracellular vesicles (Morelli et al 2019 ) and non-coding RNAs (Castillo-Casas et al 2023 ; Jankauskas et al 2023 ), cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%